Towards the development of a model of user engagement with packaged software - Finnerty, Cecilia (2001)
This thesis draws on the body of knowledge in the field of HCI to develop a model of User Engagement with software with the aim of assisting organisations, which do not develop software in-house, in determining the level of user engagement with a software product prior to its introduction. It then goes further to develop the basis of an instrument for measuring that engagement before the commitment to purchase a software package. If an individual is happy with a piece of software, he is more likely to use it productively. If an organisation can assess the level of engagement with software prior to its introduction, it may take corrective action to ensure that its introduction is successful. The focus is on multi-user software of which usage is mandatory.